Tuberculous Dactylitis" (Spina Ventosa) in a 19 years old boy - a very rare disease (KYAMC Journal, 2017)
Tuberculous Dactylitis is an unusual form of osteoarticular tuberculosis, involving the short bones of the hand & feet. Hence it is also known spina vantosa. In our case, a 19 years old boy presented with a swelling in the middle part of right ring finger which was provisionally diagnosed as a Giant cell tumor while the possibility of spina ventosa (Tubercular dactylitis) was kept in mind. He was admitted for curettage of the phalanx followed by bone grafting. Histopathological examination report confirmed it as Spina ventosaKYAMC Journal Vol. 7, No.-1, Jul 2016, Page 726-728